A CLINICAL COMPARATIVE STUDY OF SCALP BLOCK WITH 0.5% BUPIVACAINE VERSUS LEVOBUPIVACAINE 0.5% FOR MAYFIELD INSERTION ON HAEMODYNAMIC RESPONSE AND EFFICACIES OF POSTOPERATIVE ANALGESIA - RAMESH, KALAPALA; EMEEMA, BANDRAPALLI; PRIYADARSHINI, K. INDIRA; VALLEPALLI, CHANDRASEKHAR; YELURU, MADHULIKA (International Journal of Current Pharmaceutical Research, 2024)
Objective: Present study was performed to compare the effectiveness of 0.5% bupivacaine hydrochloride and 0.5% levobupivacaine for scalp block on the haemodynamic response, efficacy and additional analgesic requirement of these drugs in the post operative period during Mayfield insertion for craniotomy. Methods: 60 patients of American society of anaesthesiologists physical status Ⅰ and Ⅱ who underwent elective craniotomies were randomly divided into two groups Group B (n=30) who received scalp block with 0.5% bupivacaine hydrochloride 25 ml, Group L (n=30) received 25 ml of 0.5% levobupivacaine 5 min prior to Mayfield insertion. Mean arterial pressure (MAP), pulse rate, pain score (VAS score), additional intraoperative and postoperative analgesic requirement were recorded at different time points. Results: Pulse rate, mean arterial pressure were stable during and after Mayfield insertion in both groups at all time points. Conclusion: Both bupivacaine and levobupivacaine for scalp block are equally effective in attenuating haemoynamic responses during Mayfield insertion. Levobupivacaine being less toxic can be a safe alternative for scalp block.